2012
DOI: 10.1002/prot.24141
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions play an essential role in the binding of oleic acid with α‐lactalbumin in the HAMLET‐like complex: A study using charge‐specific chemical modifications

Abstract: Human α-lactalbumin made lethal to tumor cells (HAMLET) and its analogs are partially unfolded protein-oleic acid (OA) complexes that exhibit selective tumoricidal activity normally absent in the native protein itself. To understand the nature of the interaction between protein and OA moieties, charge-specific chemical modifications of lysine side chains involving citraconylation, acetylation, and guanidination were employed and the biophysical and biological properties were probed. Upon converting the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…We cautiously speculate that this could also be the case for 20 °C, because electrostatic encounter of deprotonated sulfonic acid groups of ANS molecules to positively charged surface residues of a population of native‐like BLA may need to involve the release of water molecules as well. A similar hypothesis of electrostatic interactions between native BLA and ionized oleic acid was proposed recently (Xie et al ., ; Park et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We cautiously speculate that this could also be the case for 20 °C, because electrostatic encounter of deprotonated sulfonic acid groups of ANS molecules to positively charged surface residues of a population of native‐like BLA may need to involve the release of water molecules as well. A similar hypothesis of electrostatic interactions between native BLA and ionized oleic acid was proposed recently (Xie et al ., ; Park et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Considerable attention has been given to this molten globular or partially unfolded apo-state of human α-LA because of its ability to form a protein-fatty acid complex with oleic acid (C18: 1,9 cis) (Håkansson et al, 1995). Known as human alpha-lactalbumin made lethal to tumor cells (HAMLET) or BAMLET (its bovine protein counterpart) (Svensson et al, 2000), the interesting properties of its tumor-selective cytotoxicity have brought about active investigations on the cell biology (Svensson et al, 2003a;Mossberg et al, 2010;Brinkmann et al, 2011;Min et al, 2012) as well as its structural characterization (Svensson et al, 2003b;Knyazeva et al, 2008;Xie et al, 2013). Between α-LA and oleic acid, oleic acid appears responsible for the cellular cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The data indicated that a fatty acid was present in the samples; however, it was not possible to determine whether the OA present in the sample was bound to the protein and was therefore cytotoxic. To determine whether the sucrose present impedes the cytotoxicity of the gastric aspirates, a cell viability assay was performed against U2OS, a human osteosarcoma cell line that is sensitive to HAMLET and BAMLET (31) , using BAMLET with and without added sucrose. No difference was observed in the activity of BAMLET after the addition of sucrose, indicating that the presence of sucrose in the samples did not affect the cytotoxicity of the samples and confirming that the complex was not formed under the in vivo conditions of the assay.…”
Section: Cytotoxicity Measurementsmentioning
confidence: 99%
“…HAMLET was shown to have very fluctuating structure: it has a near‐UV CD spectrum similar to the molten globule , a melting temperature 15 °C lower than the apo‐form and a greater flexibility than the apo‐ and holo‐states of α‐LA in terms of hydrogen/deuterium exchange and proteolysis . Proteolysis experiments suggest that contacts between OA and α‐LA mainly occur via the α‐helical domain , whereas chemical modification studies reveal that α‐LA:OA interactions, and thus the ability to form cytotoxic complexes, involve positive amino acid side chains . Equine lysozyme, a homologue to α‐LA can form complexes with OA (termed ELOA) by the same chromatographic approach .…”
Section: Preparation Of Cytotoxic α‐La:oa Complexes By Different Apprmentioning
confidence: 99%